Analysis of the Impact of Debt on Student Friendships from an Islamic Perspective - Putri, Fannya Regina; Utami, Febrina Amelia; Nasir, Latifah Azzahra; Limbong, Karina Lolo; Siregar, Hapni Laila (International Journal of Education, Information Technology, and Others, 2024)
In Islam, debt is not just a material transaction, but also a moral bond that requires honesty, trustworthiness and responsibility. Lenders who behave well and wisely will be greatly rewarded. However, for those who refuse or fail to repay the debt properly, there is a great threat. Therefore, it is important for all of us to observe the Shari'a correctly in matters of debt. The problem in this study is the effect of debt on friendship relationships seen from the point of view of Islamic teachings, with a sample of 100 students of Medan State University. This research method uses a quantitative method, with data collection techniques in the form of a questionnaire or questionnaire analyzed using SPSS. From the results of the research conducted, it shows that the Sig value for influencing debt on friendship relationships is 0.000 <0.05 and the Thitung value is 16,729> Ttabel 1,985. So it can be stated that debt has a positive and significant effect on friendship relationships, so it can be stated that debt greatly affects friendship relationships.